Exponential growth of dental schools in Chile: effects on academic, economic and workforce issues - Ricardo Andres Cartes-Velasquez (Sociedade Brasileira de Pesquisa Odontológica, 2013)
In the last 30 years, Chile has undergone noteworthy economic development and an exponential growth in the access of its population to higher education. The aim of this paper was to review the changes in academic, economic and workforce issues that occurred as a consequence of the growth in supply of undergraduate dental vacancies between 1997 and 2011. Data collected from the Consejo de Educación Superior - CES, Comisión Nacional de Acreditación - CNA, and Instituto Nacional de Estadísticas de Chile - INE included these variables: number of dental schools, school type (private or traditional, see explanation below), city where the school is located, entry vacancies, total student enrollment, admission scores, percentile rank of dentistry as a university career, tuition fees, accreditation status, and number of inhabitants. There was an exponential increase in dental schools in Chile (5 to 34) that occurred in association with the rise in tuition fees (US$ 3900 to US$ 9800), a deterioration in the academic level of dental students (650 to 550 points in admission scores) and a predicted 77.5% oversupply of dentists by 2025, according to WHO criteria. The exponential increase in dental schools in Chile brought about negative consequences, such as increasing career costs, deterioration in the academic level of dental students, and an oversupply of dentists, associated with lower incomes and possibly leading to unemployment. Additional research should be conducted to determine whether an increase in the number of dentists can improve the population's access to dental care and reduce the oral disease burden.